(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2026)
This study uses a traditional Indian fermentation method with fresh curd made through household back-slopping as the only inoculum to create millet-based probiotic foods. Three types of fermented products: lassi, porridge, and gruel from sorghum, pearl millet, and finger millet were prepared. The process reflects established home practices while incorporating modern evaluation methods. A total of 36 formulations were systematically designed by changing millet type, substrate type (flour, extract, or residue), and pretreatments, including germination, gelatinization, and adding dairy milk. This approach enabled targeted assessment of how each variable affects nutritional, functional, and sensory qualities. Fermentation improved probiotic quality (LAB >10⁶ CFU/mL), mineral bioavailability (Fe, Mn, Cu, Zn), antioxidant capacity, reducing sugars, and protein content. Germination raised phenolic and antioxidant levels with increased water and oil absorption. Gelatinization enhanced texture and stability, especially in porridge and gruel. Both germination and fermentation reduced sedimentation, boosting product stability. Adding dairy milk improved sensory acceptance, particularly in lassi. Following circular bioeconomy principles, the insoluble residue from extracting millet milk is converted into gruel. This ensured complete use of raw materials and minimized waste. By extending a familiar and tested dairy fermentation method to underused millets, this work connects traditional knowledge with scientific support. It offers functional, probiotic-rich foods that promote nutritional security and zero-waste processing while encouraging small-scale, home-based food ventures.